Interferon-Combination Strategies for the Treatment of Chronic Hepatitis C - Aronsohn, Andrew; Jensen, Donald (Seminars in Liver Disease, 2014)
Direct acting antiviral agents have revolutionized hepatitis C (HCV) therapy. Many agents that are either currently available or undergoing investigation offer higher rates of sustained virologic response, reduced toxicity and shorter duration of therapy when compared to traditional treatment consisting of pegylated interferon and ribavirin. Although interferon free therapy may be a preferred option, some patients may still require an interferon based regimen to ensure efficacy. In this review, we discuss therapeutic strategies which utilize various combinations of protease inhibitors, NS5A inhibitors, nucleotide polymerase inhibitors and non-nucleoside polymerase inhibitors along with pegylated interferon in the treatment of chronic HCV.
Keywords: hepatitis C; hepatitis C therapy; direct-acting antiviral agents